From the Great Nationalism to Narrower Ethnonationalism in Post-1991 Ethiopian Federalism: Counter Narrative Advent of the Amhara Ethnic Nationalist Movements - Tareke, Sibuh Gebeyaw (Research in Business and Management, 2023)
Ethiopia is a multiethnic and multi-linguistic state. The country’s political history has shown that it has been an empire state since ancient times. However, its diverse ethnic groups existed together as Ethiopian nationalists. Following the introduction of the socialist-oriented federal state in 1991, ethnonational movements took place in Ethiopian politics. The 1995 FDRE constitution gives the sovereign power to "nations, nationalities, and peoples" to maintain unity along with diversity. It also created ethnic federalism-based territorial units to liberate other ethnic groups from the past Amhara ’Neftegna’ domination system. However, the recognition of these rights has promoted ethnonationalism rather than Ethiopianism. And also creates a tendency in other regions as Amharans have historically oppressed the different ethnic groups. Thus, the Amhara people who live in other areas have been discriminated against. This phenomenon has intensified the advent of Amhara nationalist movements. This study explores the theoretical frameworks of ethnonationalism and federalism. It also examined the causes and impacts of the deterioration of Ethiopianism and the advent of the Amhara nationalist movements in the case study areas. In the end, it provides mechanisms to maintain unity along with diversity in future Ethiopia.